TRADE, TAXATION, AND THE ENVIRONMENT: POSSIBLE IMPACTS OF INDIA – SOLAR CELLS ON BRAZILIAN TAX INCENTIVES FOR THE SOLAR ENERGY SECTOR - Cavalcante, Denise Lucena; de Oliveira, Mônica Rocha Victor (Novos Estudos Jurídicos, 2018)
In 2013, the U.S. filed a complaint against India before the World Trade Organization, alleging the inconsistency of certain measures for India relating to domestic requirements under the Jawaharlal Nehru National Solar Mission (“NSM”) for solar cells and solar modules with the rules of the GATT, the SCM and the TRIMS (WTO/DS456).